Protocol for developing a core outcome set for male infertility research: an international consensus development study - Rimmer, Michael P (2022)
We aim to develop, disseminate and implement a minimum data set, known as a core outcome set, for future male infertility research. Research into male infertility can be challenging to design, conduct and report. Evidence from randomized trials can be difficult to interpret and of limited ability to inform clinical practice for numerous reasons. These may include complex issues, such as variation in outcome measures and outcome reporting bias, as well as failure to consider the perspectives of men and their partners with lived experience of fertility problems.